Islamic librarianship and Malaysian Islamic libraries - Suja', Balqis (Read Resources Sdn. Bhd., 2012)
The book presents a brief overview of the existence of Islamic libraries, past and present. The discussion on the emergence, history and development of Islamic libraries is hoped to enlighten readers on the need to consider Islamic librarianship as a specialisation within library and information studies. A literature survey was carried out to determine the characteristics of Islamic libraries and identify topics for gauging awareness on Islamic libraries’ requirements and provide a strategy for its development. Selected topics and issues include perspectives on the services and collections, organisation and access, professionalism of Islamic librarianship, impacts of technology on Islamic libraries and direction for research. A hint on the Malaysian scenario relevant to Islamic libraries development is supplemented with an appendix of a list of more than 200 Islamic libraries in Malaysia, categorised into six organisation types at the end of this book.